MOTIVATION AND HESITANCY TOWARDS THE COVID-19 VACCINE IN EXPECTING MOTHERS - Dora Samaria; Nisrina Puspaningrum (Poltekkes Kemenkes Semarang, 2023)
The practical and efficient prevention of the transmission of COVID-19 infection is through vaccination. However, there are challenges associated with refusing or postponing vaccination due to skepticism regarding the efficacy and safety of vaccines, particularly among pregnant women. The risk factors of pregnant women tend to make this vulnerable group reluctant to uptake the vaccines. Motivation influences personal hesitancy in deciding, especially regarding the COVID-19 vaccine. Therefore, this study investigated the correlation between motivation and hesitancy related to COVID-19 vaccines in expectant mothers at the Bening Nawangsari Midwife Clinic, Bekasi City. In this cross-sectional study, as many as 301 pregnant mothers were chosen using the consecutive sampling method. The Motivations of Vaccination Questionnaire and The Reasons for Hesitation Questionnaire were employed when collecting the data. After calculating the data with the Chi-Square test, a significant relationship between motivation and vaccine hesitancy was revealed (p-value= 0.001). It was concluded that there was a significant relationship between expectant mothers' motivation and hesitation to receive the COVID-19 vaccine.